2019
DOI: 10.1002/we.2405
|View full text |Cite
|
Sign up to set email alerts
|

Wind farm generation forecast and optimal maintenance schedule model

Abstract: Wind farms must periodically take their turbines offline in order to perform scheduled maintenance repairs. Given that these interruptions impact energy generation and that under Power Purchase Agreements productions shortfalls must be replaced by energy purchases in the spot market, the optimal time to begin maintenance work in a wind farm is a function of both the expected wind speeds and electricity spot prices. In this article, we develop a model to determine the optimal maintenance schedule of a wind farm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…We also analyzed the sensitivity of returns in relation to the expected level of liquidity, given the characteristics of the Brazilian market, and we evaluated the option of taking out insurance to protect the clearing house. The insurance premium was calculated using a Monte Carlo simulation, a well-established and widely used method in studies of derivatives and futures markets, used in studies such as those of Irwin et al (1996), Cortazar and Schwartz (1998), Abadie and Chamorro (2009) and Pelajo et al (2019). The analysis of the simulation results and the insurance calculation are new and important information for market agents interested in the creation of a Brazilian electricity futures clearing house.…”
Section: Introductionmentioning
confidence: 99%
“…We also analyzed the sensitivity of returns in relation to the expected level of liquidity, given the characteristics of the Brazilian market, and we evaluated the option of taking out insurance to protect the clearing house. The insurance premium was calculated using a Monte Carlo simulation, a well-established and widely used method in studies of derivatives and futures markets, used in studies such as those of Irwin et al (1996), Cortazar and Schwartz (1998), Abadie and Chamorro (2009) and Pelajo et al (2019). The analysis of the simulation results and the insurance calculation are new and important information for market agents interested in the creation of a Brazilian electricity futures clearing house.…”
Section: Introductionmentioning
confidence: 99%
“…The results demonstrated that non-parametric based combined models usually have a better performance than other models. Jonas C. Pelajo et al (2019) developed a model to predict wind speed and energy price to determine the optimal maintenance planning of a real wind farm in the Brazilian Northeast [23]. Osório et al (2014) proposed a combined forecasting model based on mutual information, wavelet transform, particle swarm optimization, and adaptive neuro-fuzzy inference system framework to predict the short-term wind power and electricity market prices [24].…”
Section: Introductionmentioning
confidence: 99%
“…e time series methods model the relationship between current wind speeds and historical wind speeds, which are suitable for short-term and medium-term forecast. Most time series methods, such as the autoregressive integrated moving average (ARIMA) [2,13] and autoregressive moving average with exogenous variables (ARMAX) [14], assume that there is a linear relationship between current data and past data or errors. e construction, order identification of these models is easy to understand, but their linear assumptions lead to poor forecast performance on nonlinear data.…”
Section: Introductionmentioning
confidence: 99%